2009
DOI: 10.1093/plankt/fbp121
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase of the diatom Skeletonema marinoi influences the metabolic profile of the cells and the selective feeding of the copepod Calanus spp.

Abstract: Copepods dominate the biomass of marine zooplankton and through their prey selection they act as top-down regulators of planktonic communities. We investigated feeding preference of copepods in the presence of the diatom Skeletonema marinoi at different time points throughout the development of a bloom and a culture. Quantitative PCR gut content assessment revealed that the food uptake of the copepod Calanus spp. on mixed diets and on artificially induced mesocosm blooms was selective. Uptake of S. marinoi was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 38 publications
4
51
1
Order By: Relevance
“…In the recent study of Barofsky et al (2010), other potential food sources (ciliates and dinoflagellates) were present in the mesocosm, but these could not mask the preferences of the planktonic calanoid copepod Calanus for cells of the planktonic diatom Skeletonema marinoi in the late stationary phase. However, since Barofsky et al (2010) measured only diatom DNA, there was no quantification of the role of other food sources.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the recent study of Barofsky et al (2010), other potential food sources (ciliates and dinoflagellates) were present in the mesocosm, but these could not mask the preferences of the planktonic calanoid copepod Calanus for cells of the planktonic diatom Skeletonema marinoi in the late stationary phase. However, since Barofsky et al (2010) measured only diatom DNA, there was no quantification of the role of other food sources.…”
Section: Discussionmentioning
confidence: 97%
“…Planktonic copepods, however, have the additional ability to select diatoms based on their growth phase (Barofsky et al 2010), which is known to be associated with marked differences in exometabolite production (Ba rofs ky et al 2009). The resulting complex chemical sphere around phytoplankton cells, the socalled exo metabolome or phycosphere (Moore et al 1999), might have important implications for the organisms grazing on the cells (see Barofsky et al 2010). Since the composition of the phycosphere changes over time, it has the potential to transmit information on the physiological state of the cell to grazing copepods (Moore et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is mainly a size-selective grazer, preferring larger cells such as diatoms or microzooplankton (see Hansen et al 1994, Nejstgaard et al 2001b, Calbet & Saiz 2005. Using the quantitative PCR method, Barofsky et al (2010) reported that C. finmarchicus showed feeding levels at least as high on the diatom Skeletonema marinoi as on the smaller cryptophyte Rhodomonas marina. As we used labeled Rhodomonas sp., the total ingestion rates presented here should be taken as a conservative estimate.…”
Section: Copepod Feeding and Carbon Requirementsmentioning
confidence: 99%
“…Metabolomics is also increasingly applied, as a tool, in ecological and evolutionary studies (Macel et al, 2010). Only a few metabolomics studies have so far been performed on microalgae grown in different environmental conditions (Bo¨lling & Fiehn, 2005) or on the metabolite profiles of the different growth stages of microalgae (Barofsky et al, 2009(Barofsky et al, , 2010Vidoudez & Pohnert, 2012). Chemotaxonomic studies using metabolomic data on microalgae have been shown to be promising in species discrimination using NMR spectroscopy (Chauton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%